2017
DOI: 10.1093/infdis/jix627
|View full text |Cite
|
Sign up to set email alerts
|

Early Cutaneous Leishmaniasis Patients Infected With Leishmania braziliensis Express Increased Inflammatory Responses After Antimony Therapy

Abstract: The enhanced production of proinflammatory cytokines, due in part to the decreased ability of IL-10 to down-modulate immune response during therapy in ECL, promotes the development and persistence of leishmania ulcer despite antimony therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 47 publications
1
28
1
Order By: Relevance
“…But, until now it has not been possible to accomplish a new treatment with less toxicity and at least the same efficacy of the old available drugs. It is important to note that, in parallel to treatment failure, the literature has also evidenced the possibility of an early spontaneous healing without treatment ( Oliveira-Ribeiro et al, 2017 ; Costa et al, 2018 ). In this context, understanding why leishmaniasis is becoming difficult to treat and control can help to develop new approaches to improve the healing of this infection.…”
Section: The Problemmentioning
confidence: 99%
“…But, until now it has not been possible to accomplish a new treatment with less toxicity and at least the same efficacy of the old available drugs. It is important to note that, in parallel to treatment failure, the literature has also evidenced the possibility of an early spontaneous healing without treatment ( Oliveira-Ribeiro et al, 2017 ; Costa et al, 2018 ). In this context, understanding why leishmaniasis is becoming difficult to treat and control can help to develop new approaches to improve the healing of this infection.…”
Section: The Problemmentioning
confidence: 99%
“…The performance of adaptive immune responses in the cicatrization processes is well studied . However, the role of innate immunity in response to antimony treatment needs to be better investigated . Monocytes play an intriguing role in CL because they are host cells for the parasites and at the same time immune response regulating cells equipped to destroy Leishmania .…”
Section: Introductionmentioning
confidence: 99%
“…Monocytes play an intriguing role in CL because they are host cells for the parasites and at the same time immune response regulating cells equipped to destroy Leishmania . It has been described that, after treatment, these cells are activated by IFN‐γ produced by CD4 + and CD8 + T lymphocytes and NK cells and induced to produce TNF that, in synergy with IFN‐γ, activate iNOS to produce NO, which is responsible for the destruction of amastigote forms . Studies have focused on determining important aspects of the immune response in CL as mechanisms associated with natural resistance, the presence of active lesions, and healing after treatment .…”
Section: Introductionmentioning
confidence: 99%
“…The percentage of failure to therapy was lower than we have usually observed that similar to previous studies. We believe that the limited number of participants of the study was responsible for these differences ( 28 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Between the years 2012 and 2017, 6,597 cases of ATL were reported in the region of Corte de Pedra. As other endemic foci , the cure rates of antimonial pentavalent (Sbv) declined from 90 to 50% in the last 30 years ( 28 30 ).…”
Section: Methodsmentioning
confidence: 99%